1986
DOI: 10.1177/074193258600700304
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Handicapping Conditions Among Juvenile Delinquents

Abstract: Information regarding the prevalence of handicapping conditions among juvenile delinquents is scattered throughout various educational and correctional journals and institutional and governmental reports. Research on this topic has been sporadic, and results of studies have been inconsistent. Nevertheless, taken together the studies suggest that a high percentage of young offenders are indeed handicapped, and that the prevalence of certain disabilities may be much greater among this population than among the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 32 publications
3
26
0
Order By: Relevance
“…Estimates of the number of youths within the U.S. juvenile justice system who have been diagnosed as having a 'disability' ranges from 30% to 60% of the entire juvenile justice population (e.g., Morgan, 1979;Rutherford et al, 1985;Murphy, 1986;Bullis & Yovanoff, 2005;Baltodano et al, 2005;Quinn et al, 2005). A study focusing on the Virginia Department of Juvenile Justice reported that more than 40% of juveniles met special education criteria (McGarvey & Waite, 2000).…”
Section: School Issuesmentioning
confidence: 98%
“…Estimates of the number of youths within the U.S. juvenile justice system who have been diagnosed as having a 'disability' ranges from 30% to 60% of the entire juvenile justice population (e.g., Morgan, 1979;Rutherford et al, 1985;Murphy, 1986;Bullis & Yovanoff, 2005;Baltodano et al, 2005;Quinn et al, 2005). A study focusing on the Virginia Department of Juvenile Justice reported that more than 40% of juveniles met special education criteria (McGarvey & Waite, 2000).…”
Section: School Issuesmentioning
confidence: 98%
“…(Murphy, 1986) Literature review 22% -90.4% (Murray, 1976) Literature review (Crawford, 1982b) National Center for State Courts (NCSC) studies (Broder, Dunivant, Smith, & Sutton, 1981;Dunivant, 1984;Keilitz & Dunivant, 1986;Zimmerman, Rich, Keilitz, & Broder, 1981) 10.6% -90.4% 33% -36% 16 -19% The significant discrepancy between prevalence reports has been attributed to a number of factors: (a) inconsistent definitions (Murphy, 1986: Murray, 1976, (b) procedural methods and data analysis (Murray, 1976), (c) lack of uniform assessment criteria (Murphy, 1986), (d) variance of age groups classified as juvenile (Murphy, 1986), and (e) variance of offender characteristics, i.e., status regarding seriousness and number of offenses and incarceration (Murphy, 1986). High prevalence estimates have led educators, parents, and the juvenile justice system to be concerned about a possible link between learning disabilities and juvenile delinquency.…”
Section: Prevalence Estimates Of Learning Disabilities In Delinquentsmentioning
confidence: 99%
“…These youth are more likely to be African American and male (Zabel & Nigro, 1999). As many as 13% of delinquent youth demonstrate a serious learning disability (Murphy, 1986;Quinn et al, 2005;Rutherford, Nelson, & Wolford, 1985), but the direct relationship between learning disabilities and delinquency is not well understood (Brier, 2001;Malmgren, Abbott, & Hawkins, 1999).…”
mentioning
confidence: 96%